CANCER TREATMENT-RELATED CARDIOTOXICITY: OPTIMIZING HEART HEALTH FROM DIAGNOSIS TO LONG-TERM FOLLOW-UP - Melissa M. Hudson, MD (Hematology, Transfusion and Cell Therapy, 2023)
Improvements in overall survival rates for children diagnosed with cancer have led to a growing number of long-term childhood cancer survivors and an increasing recognition of the late health conditions they may experience. Among these are cardiac conditions, most commonly associated with prior anthracycline chemotherapy and chest-directed radiation exposing the heart. Potential late effects of anthracycline chemotherapy and chest-directed radiation therapy include cardiomyopathy, subclinical left ventricular dysfunction, heart failure, and arrhythmia. In addition, chest-directed radiation exposing cardiac substructures has been associated with risk for pericarditis, pericardial fibrosis, valvular disease, atherosclerotic heart disease and myocardial dysfunction. Patient (e.g., age at exposure, family history, genetic variation) and treatment (e.g., cumulative dose, multimodality cardiotoxic therapy) factors influence the magnitude of risk. In addition, co-morbid medical conditions (e.g., hypertension, diabetes, dyslipidemia, obesity) and health behaviors (e.g., smoking) can exacerbate risk in aging survivors. Recognition of treatment associations and adverse cardiac outcomes has informed risk-stratification strategies used in contemporary protocols and guided health surveillance recommendations for long-term survivors. Dexrazoxane has also been used for primary prevention of anthracycline cardiotoxicity in high exposure groups. Screening guidelines recommend frequency-adapted (based on cumulative cardiotoxic exposures) echocardiography to facilitate early identification of cardiomyopathy as well as attention to modifiable cardiovascular disease risk factors and health behaviors. This presentation will provide an overview of cardiotoxic cancer treatment modalities and current approaches to prevent cardiac disease and preserve cardiac function.